Follicular fluid and assisted reproductive technology programs outcomes (literature review) - Anna G. Burduli; Natalia A. Kitsilovskaya; Yuliya V. Sukhova; Irina A. Vedikhina; Tatiana Y. Ivanets; Vitaliy V. Chagovets; Nataliia L. Starodubtseva; Vladimir E. Frankevich (IP Berlin A.V., 2020)
The review presents data on metabolites in the follicular fluid (FF) from the perspective of reproductive medicine and their use in order to predict outcomes of assisted reproductive technology (ART) programs. It considers various components of this biological medium (hormones, lipids, melatonin, etc.) with an assessment of their predictive value in prognosis of the effectiveness of in vitro fertilization (IVF) programs. The data on experimental directions in this field and the prospects for their use in clinical practice are presented. The article emphasizes that the growing clinical need and the unsolved problem of increasing the effectiveness of ART programs determine the need for further studies of the FF composition. Materials and methods. The review includes data related to this topic from foreign and Russian articles found in PubMed which were published in recent years. Results. Given the established fact of a direct effect of FF composition on growth and maturation of oocytes, and further, on the fertilization process, various FF metabolites are actively investigated as non-invasive markers of quality of oocytes/embryos. The article provides data on the experimental directions in this field and the prospects for their use in clinical practice. However, clinical studies of a relation between various FF metabolites levels and outcomes of IVF programs are contradictory. Conclusion. Owing large economic cost for treatment of infertility with IVF, there is need for expansion and intensification of studies to identify and use reliable predictors in prognosis of ART programs outcomes.